Biochemical Biomarkers and Neurodegenerative Diseases - Ciaccio, Marcello (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this book, we collected scientific articles, including reviews and research articles, showcasing the lastest literature on the importance of biochemical biomarkers in the management of neurodegenerative diseases, from screening to diagnosis, prognosis, and treatment.